(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Aim of the paper is to read the past, present and future of the energy scenario in India. Study takes into account India’s ongoing requirement of energy, its domestic generation potentiality and its changing pattern of energy source destinations. Research output depicts that growing economic activities demanded huge supply of energy. India met its energy demand since 1940 onwards from various destinations. Simultaneously the difference between energy demand and supply is not only met from imports but also by constant energy policies. It has been identified that over the years the power generation in India increased at CAGR of 5.69 Percent. However India’s major electrification is done from coal, currently the total installed coal thermal power capacity registered about 191.09GW.